Research on selection in an international context: Current status and future directions - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2007)
Due to the globalization of the economy, organizations continue to move beyond national borders. This is reflected in international collaborations, joint ventures, strategic alliances, mergers, and acquisitions. As a consequence, it is necessary for organizations to view the labor market in an international scope. In addition, there is a need for HR systems that can be used across multiple countries while at the same time recognizing local particularities (Schuler, Dowling, & DeCieri, 1993). One of these HR challenges is selecting people in an international labor market.